The effect of MitraClip mitral valve repair on a number of ventricular tachycardia episodes. (14th October 2021) - Hudec, M; Januska, J; Jiravsky, O; Kala, P; Kufova, P; Konderlova, L; Stepanova, R; Muchova, T; Kubat, T; Sknouril, L
Abstract: Background: Mitral valve repair with MitraClip is an established method in the treatment of severe mitral regurgitation. Effect on mitral regurgitation severity, NYHA class and left ventricular function is known, as well as on mortality and number of hospitalizations. Otherwise, there is a lack of evidence, if a successful repair can affect the number of episodes of malignant arrhythmias. Purpose: To compare the number of ventricular arrhythmias and ICD therapies before and after successful mitral valve repair with MitraClip in retrospective analysis. Methods: We analysed patients after a MitraClip mitral valve repair in whom an ICD was implanted at least 1 month before the procedure. Out of 217 patients, there were 47 with ICD, traceable history and successful repair (MR grade ≤2.5 after the procedure). We searched all recorded ICD controls for evidence of ventricular arrhythmias and ICD therapies (ATP or shock). Statistical analysis was performed comparing the number of ventricular arrhythmias and ICD therapies "per month-per patient" before and after the procedure. Results: We didn't found any statistical difference in number of malignant arrhytmia events before and after the procedure (mean 0.024±0.069 vs 0.029±0.079, p=0.46), neither in ATP therapies (mean 0.038±0.146 vs 0.542±3.249, p=0.39) nor in shocks (mean 0.063±0.225 vs 0.148±0.499, p=0.33). After dividing patients into two groups – with or without previous myocardial infarction, there was also no statistical difference in both groups. In "MI" group: a number of ventricular arrhythmia (mean 0.016±0.036 vs 0.016±0.047, p=0.95), ATP therapies (mean 0.029±0.109 vs 0.073±0.285, p=1.0), shocks (mean 0.049±0.184 vs 0.048±0.172, p=0.77). In "no MI" group: a number of ventricular arrhythmia (mean 0.035±0.098 vs 0.047±0.108, p=0.22), ATP therapies (mean 0.05±0.19 vs 1.203±5.024, p=0.16), shocks (mean 0.083±0.277 vs 0.289±0.733, p=0.17). Conclusion: Our results don't reflect any influence of MitraClip mitral valve repair on ventricular arrhythmias, ATP therapies or shocks before and after the procedure. Another and deeper analysis should be performed to understand these results. Funding Acknowledgement: Type of funding sources: None.